An appraisal of the Suzuki cross-coupling reaction for the synthesis of novel fluorescent coumarin derivatives - Alhaj Zen, Amer; Aylott, Jonathan W.; Chan, Weng C. (Elsevier, 2014)
We report the chemical design and development of 3-aryl-substituted 7-alkoxy-4-methylcoumarins with enhanced fluorogenic properties. The 3-aryl substituents are installed via an optimized Suzuki–Miyaura cross-coupling (SMC) reaction between a 7-alkoxy-3-bromo-4-methylcoumarin and aryl boronic MIDA esters using Pd(OAc)2/XPhos in a catalytic system with K2CO3 in aqueous THF. Under these conditions, an exocyclic ester functionality is found to be unaffected. Subsequent saponification revealed a carboxylic acid functionality that is suitable for conjugation reactions. Evaluation of their fluorescence properties indicated that the installed 3-heteroaryl substituent, particularly benzofuran-2-yl, resulted in a significant red shift of both the excitation and emission wavelengths.